3‐Level Envelope Delta‐Sigma Modulation RF Signal Generator for High‐Efficiency Transmitters. Issue 6 (1st December 2014) - Seo, Yongho; Cho, Youngkyun; Choi, Seong Gon; Kim, Changwan
Abstract : This paper presents a 0.13 μm CMOS 3‐level envelope delta‐sigma modulation (EDSM) RF signal generator, which synthesizes a 2.6 GHz‐centered fully symmetrical 3‐level EDSM signal for high‐efficiency power amplifier architectures. It consists of an I‐Q phase modulator, a Class B wideband buffer, an up‐conversion mixer, a D2S, and a Class AB wideband drive amplifier. To preserve fast phase transition in the 3‐state envelope level, the wideband buffer has an RLC load and the driver amplifier uses a second‐order BPF as its load to provide enough bandwidth. To achieve an accurate 3‐state envelope level in the up‐mixer output, the LO bias level is optimized. The I‐Q phase modulator adopts a modified quadrature passive mixer topology and mitigates the I‐Q crosstalk problem using a 50% duty cycle in LO clocks. The fabricated chip provides an average output power of –1.5 dBm and an error vector magnitude (EVM) of 3.89% for 3GPP LTE 64 QAM input signals with a channel bandwidth of 10/20 MHz, as well as consuming 60 mW for both channels from a 1.2 V/2.5 V supply voltage.